2015
DOI: 10.2320/jinstmet.jb201511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Al and Cu Contents on Mechanical Properties of Au-Cu-Al Shape Memory Alloys

Abstract: In order to develop high performance biomedical shape memory alloy having both good biocompatibility and high X ray radiography resolution, effects of Al and Cu contents on the martensitic transformation, microstructure and mechanical properties of AuCuAl ternary alloys were studied. Differential scanning calorimetry revealed that the martensitic transformation start temperature decreased with a rate of -7 K/molAl in the Au 30 molCu Al alloys. Besides, the M s increased with a rate of 18 ~53 K/molCu in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Microstructure of 25Cu was reported. 13) Figure 3 shows stress-strain curves by the compression tests at 298 K. All of the alloys, except 40Cu, did not break during the compression but showed plastic deformation. Especially, 25Cu, 30Cu and 45Cu had good compressive deformability over 5%, and these results were quite different from those obtained by tensile tests.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microstructure of 25Cu was reported. 13) Figure 3 shows stress-strain curves by the compression tests at 298 K. All of the alloys, except 40Cu, did not break during the compression but showed plastic deformation. Especially, 25Cu, 30Cu and 45Cu had good compressive deformability over 5%, and these results were quite different from those obtained by tensile tests.…”
Section: Methodsmentioning
confidence: 99%
“…Especially, 25Cu, 30Cu and 45Cu had good compressive deformability over 5%, and these results were quite different from those obtained by tensile tests. 13) Therefore, it was revealed that (1) intergranular fracture is well suppressed during compression, and (2) Au 2 CuAl is not intrinsically brittle when grain boundary fracture is suppressed. Moreover, 25Cu, 30Cu and 45Cu all exhibited a two-stage yielding behavior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shape memory alloys can be classified into the following groups according to the nature of the chemical elements found in their composition: Alloys based on Ni–Ti [ 2 , 7 , 8 , 9 ]; Copper-based alloys (Cu–Al–Zn, Cu–Al–Ni) [ 10 , 11 , 12 , 13 ]; Ferrous alloys (Fe–Mn, Fe–Ni–C) [ 14 , 15 , 16 , 17 , 18 , 19 ]; Noble alloys (Au–Cd, Ag–Cd) [ 20 , 21 , 22 ]; ”Exotic” alloys (In–Te, In–Cd, V–Nb, etc) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. …”
Section: Introductionmentioning
confidence: 99%